METAVERSE CONTRIBUTION TOWARDS SDG 9- INTERFACE AND INTERACTION - Chawla, Mamta; Sharma, Preeti; Agrawal, Ankur (International Journal of Marketing Research Innovation, 2023)
The metaverse phenomenon -- gained a lot of focus during the COVID-19 outbreak. It can be related to meeting concerns about meeting Sustainable Development Goals assigned by the United Nations. Global warming changes the local and regional ecology and is one of the significant agendas and goals related to the SDGs. It can be linked to creating industry concerns to be innovative by applying ICT to bring in development and human well-being. In this context, the application of Metaverse technology can be highlighted. Even though there are several critics of Metaverse, an attempt has been made in this work to link the usage of Metaverse application to attaining SDG number 9 of industry infra of innovative and environment-friendly processes. The information for this work has been taken from the websites, mainly accessible from India. From an economic perspective, the benefits of employing this technique out ways the social critics and contribute towards sustainable practices in terms of opportunities for optimal utilization of human capabilities and efforts, saving man-hours. Finally, user discretion in applying and adopting the latest technology must be employed to mitigate the opposing side and promote the positive impacts of its sustainable application. This research paper explores the dynamic technology landscape, focusing on applying Metaverse technology for sustainable industrial infrastructure. It categorizes existing literature into technical and application-based segments. The study addresses fundamental questions regarding Metaverse applications, stakeholders, and associated concerns to enhance our understanding of its potential impact on future global development.JEL Classification Codes: Q5, Q54, Q56, D63, O33.